FORMULASI STRATEGI PEMASARAN DENGAN PENDEKATAN SWOT DAN QSPM - Puspa, Widya; Handrito, Radityo Putro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The high national consumption pattern in the area of household products has made retail industry receives considerable supports from the government. In order to make themselves remain exist in the market, retailers, especially the traditional ones, need to apply new strategies in response to recent developments inside and outside their business. The goal of this research is to discover the appropriate marketing strategy for Green Mart by analyzing its internal and external factors. This qualitative descriptive research was organized by conducting observations, documentations, and interviews with two of the store’s staff, i.e., supervisor and operational employee, and four of its regular customers. In its collection, the data was processed and presented using the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, Strength, Weakness, Opportunity, Threat (SWOT) matrix, Internal External (IE) matrix, and Quantitative Strategic Planning Matrix (QSPM). This study finds that the applicable strategy for Green Mart is market penetration. The suggested activities are registering its brand and improving the packaging of its unbranded products, opening online stores, issuing membership cards, making contents to be uploaded in Facebook and Instagram, and hiring experts in sales promotion.